2017
DOI: 10.1038/s41467-017-01740-9
|View full text |Cite
|
Sign up to set email alerts
|

Developmental diet regulates Drosophila lifespan via lipid autotoxins

Abstract: Early-life nourishment exerts long-term influences upon adult physiology and disease risk. These lasting effects of diet are well established but the underlying mechanisms are only partially understood. Here we show that restricting dietary yeast during Drosophila development can, depending upon the subsequent adult environment, more than double median lifespan. Developmental diet acts via a long-term influence upon the adult production of toxic molecules, which we term autotoxins, that are shed into the envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
71
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 68 publications
7
71
1
Order By: Relevance
“…Finally, adults normally emerge with low hydrocarbon levels that increase dramatically over 3 days, even in the absence of food, in agreement with the hypothesis that the larval adipose cells provide the primary source of precursors for hydrocarbon production (Figures 6A and S5A). These results are consistent with previous reports, which have shown that dietary manipulation during larval life affects the blend of hydrocarbons in young adults (Stefana et al, 2017;Wicker-Thomas et al, 2015). Altogether, these observations support the model that dHNF4 mediates the rapid conversion of persisting larval fat stores into hydrocarbons shortly after adult emergence.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Finally, adults normally emerge with low hydrocarbon levels that increase dramatically over 3 days, even in the absence of food, in agreement with the hypothesis that the larval adipose cells provide the primary source of precursors for hydrocarbon production (Figures 6A and S5A). These results are consistent with previous reports, which have shown that dietary manipulation during larval life affects the blend of hydrocarbons in young adults (Stefana et al, 2017;Wicker-Thomas et al, 2015). Altogether, these observations support the model that dHNF4 mediates the rapid conversion of persisting larval fat stores into hydrocarbons shortly after adult emergence.…”
Section: Discussionsupporting
confidence: 93%
“…Drosophila continuously shed and produce hydrocarbons throughout adulthood, indicating that this biosynthetic pathway is active at later stages to maintain a hydrophobic cuticle (Stefana et al, 2017). Consistent with this, we find that oenocytespecific dHNF4 RNAi in mature adults leads to a similar degree (D) Oil Red O stains are shown for oenocytes and adult fat bodies from 3-to 5-day-old starved controls (mCherry RNAi) and starved animals with adult-specific RNAi for dHNF4, KAR, ACC, FASN CG17374 , Cpr, or Cyp4g1 in oenocytes using PromE>, Tub-Gal80 ts .…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon, first discovered in rats in 1935, has been examined by many studies in Drosophila, with a strong focus on understanding the molecular mechanisms underlying DR-induced longevity [for the first demonstration of DR in Drosophila see Chippindale et al (1993); also see Chapman and Partridge (1996), Mair et al (2003Mair et al ( , 2005 . While DR is usually implemented at the adult stage, several studies have found that a (not too strongly) restricted juvenile diet can also extend adult life span (Economos and Lints 1984;May et al 2015;Stefana et al 2017); remarkably, depending on the adult diet, larval yeast DR can double median life span, a carry-over effect caused by the larval diet-induced suppression of toxic, life span-shortening lipids produced by the adults (Stefana et al 2017).…”
Section: Quantitative Variation In Life-history Traitsmentioning
confidence: 99%
“…Early life nourishment is known to affect the adult physiology and various life-history traits in Drosophila melanogaster [1][2][3] . For example, nutrient acquisition in the form of dietary sugars (source of C) during the larval stage has contribution in egg provisioning during the early adult life of holometabolous females 4 .…”
Section: Introductionmentioning
confidence: 99%